Revalorización y sostenibilidad tecnológica de los andenes interandinos agroecológicos en la región Arequipa-Perú: Revaluation and technological sustainability of the agroecological inter-Andean terraces in the Arequipa-Peru region - León de los Santos, Nelva; Pérez Postigo, Gerber Sergio; Becerra Castillo, Sócrates; Rodríguez Quispe, Jorge Louis (Universidad del Zulia, 2021)
Cabanaconde and Ayahuasi are communities that still have ancestral customs rooted. The objective of this work was to sensitize farmers from both localities about the importance of continuing with the use of their ancestral agricultural technologies, the basis of their food security; The study was developed with a mixed approach, using qualitative techniques of the Participatory Rural Diagnosis and surveys applied to 60 farmers. The data were processed with SPSS-PASW Statistics18 software. Both communities do not present significant differences in the use of irrigation techniques, 50% of the inhabitants of Cabanaconde apply a technique under irrigation, compared to 46.7% in Ayahuasi. Regarding environmental care, 80% of the population in Ayahuasi refers to having it and 60% in Cabanaconde; 46.7% of the inhabitants of Ayahuasi and 23.3% of Cabanaconde carry out crop rotation. 66.7% of farmers in Cabanaconde and 60% in Ayahuasi do not let the soils rest after harvest. 100% of farmers in Ayahuasi and 90% in Cabanaconde, do not know about the good disposition of pesticide containers. In nutritional aspects, Cabanaconde presents 7 cases of overweight and Ayahuasi 1 case of malnutrition and 2 with overweight. In conclusion, the participatory techniques in both communities achieved positive effects of motivation and awareness. Cabanaconde y Ayahuasi son comunidades que tienen aún enraizadas las costumbres ancestrales. El presente trabajo tuvo como objetivo sensibilizar a los agricultores de ambas localidades sobre la importancia de continuar con el uso de sus tecnologías agrícolas ancestrales, base de su seguridad alimentaria; el estudio se desarrolló con un enfoque mixto, usando técnicas cualitativas del Diagnostico Rural Participativo y encuestas aplicadas a 60 agricultores. Los datos fueron procesados con software SPSS-PASW Statistics18. Ambas comunidades no presentan diferencias significativas en uso de técnicas de riego, 50% de pobladores de Cabanaconde aplica técnica bajo riego, frente al 46,7% de Ayahuasi. ...